2014
DOI: 10.1620/tjem.234.255
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-33 Promotes Disease Progression in Patients with Primary Biliary Cirrhosis

Abstract: Primary biliary cirrhosis (PBC) is a progressive autoimmune liver disease that can cause a series of complications, including cirrhosis, liver failure and hepatocellular carcinoma. Interleukin-33 (IL-33) is expressed in various non-hematopoietic cells and a certain population of immune cells, and exerts its biological effects by binding to the specific receptor, suppression of tumorigenicity 2 (ST2). A soluble form of ST2 (sST2) has been postulated to act as a decoy receptor for IL-33. In this study, we aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…30 In our present work, we demonstrate that IL-33 is elevated in cirrhotic livers, and ILC2s are upregulated, along with hepatic fibrogenesis. 31 Furthermore, ST2-deficient mice reveal that IL-33/ST2 is both required and sufficient for BDL-induced liver inflammation and fibrosis. Intraperitoneal injection of rmIL-33 induces liver inflammation in naive BL6 mice, as reported.…”
Section: Discussionmentioning
confidence: 99%
“…30 In our present work, we demonstrate that IL-33 is elevated in cirrhotic livers, and ILC2s are upregulated, along with hepatic fibrogenesis. 31 Furthermore, ST2-deficient mice reveal that IL-33/ST2 is both required and sufficient for BDL-induced liver inflammation and fibrosis. Intraperitoneal injection of rmIL-33 induces liver inflammation in naive BL6 mice, as reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported a crucial role for IL-33 in the pathology of immune-mediated liver diseases (22)(23)(24). During immunemediated hepatitis, highly elevated IL-33 levels correlated with severe liver inflammation and tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…ILC2-derived IL-5 controls eosinophil maintenance and infiltration (19,20), whereas IL-13 induces airway hyper-responsiveness (15) and contributes to parasite expulsion (21). Previous studies have implicated IL-33 in the pathogenesis of liver diseases such as chronic viral infection (22), primary biliary cirrhosis (23), and liver fibrosis (17,24). IL-33 is expressed by hepatocytes during immune-mediated hepatitis (25), but whether IL-33-elicited ILC2s contribute to disease pathogenesis has not been studied yet.…”
mentioning
confidence: 99%
“…IL‐33 has been reported to correlate with liver injury in patients with primary biliary cirrhosis (PBC) . Notably, serum levels of IL‐33 were closely associated with the degree of liver injury in patients with hepatitis B virus (HBV) infection .…”
mentioning
confidence: 99%
“…(11) IL-33 has been reported to correlate with liver injury in patients with primary biliary cirrhosis (PBC). (12) Notably, serum levels of IL-33 were closely associated with the degree of liver injury in patients with hepatitis B virus (HBV) infection. (13) Moreover, the evaluation of dynamic changes in sST2 levels in HBV acute-on-chronic liver failure showed that serum sST2 levels increased over time in patients who died during follow-up but decreased in those who survived.…”
mentioning
confidence: 99%